Energy flows along the production and use of secondary materials with a special focus on concrete - Karin Gruhler; Georg Schiller (Acta Polytechnica CTU Proceedings, 2022)
Urban mining in the existing building stock can contribute to securing raw materials and conserving natural resources if the potential of recycling construction waste is consistently exploited. From an ecological point of view, it is on the one hand interesting what amounts of primary materials can potentially be substituted and on the other how much energy need to be invested for this. At present, the recycling of construction waste usually is considered from a material perspective. There is lack of an approach, extending material-oriented considerations by energetic aspects. The aim is to develop a uniform research approach by which energy expenditure during recycling of important construction products can be determined. Besides concrete seven further construction products are  investigated. Recycling paths are described and analysed along waste management processing steps taking into account the quality of the demolition materials and the quality requirements of the possible new application variants in the construction sector. The result is a clear plea for more consistent recycling. The analyses of concrete indicate that "high-quality" recycling only results in energy advantages when "high-grade" demolition material is used. However, so-called "down-cycling" solutions allow resource conservation to be combined with energy savings, even with lower-quality demolition materials. The single-minded focus on "high-quality" recycling according to the general understanding should therefore be questioned. Instead, preference should be given to solutions that take resource conservation into account in a more holistic way especially with regard to resource conservation and climate protection.